A non-inferiority, phase III trial of gemcitabine plus capecitabine gemcitabine plus carboplatin as first-line therapy and tumor-infiltrating lymphocytes as a prognostic biomarker in patients with advanced triple-negative breast cancer - Xiaodong Liu; Weipeng Zhao; Yongsheng Jia; Yehui Shi; Xu Wang; Shufen Li; Pin Zhang; Chen Wang; Chunfang Hao; Zhongsheng Tong (Therapeutic Advances in Medical Oncology)
Background: Gemcitabine plus capecitabine (GX) shows survival benefit and manageable safety in patients with advanced triple-negative breast cancer (TNBC) but there is a paucity of phase III trial evidence. We aimed to compare the efficacy and safety of GX with gemcitabine plus carboplatin (GC) as first-line treatment for patients with advanced TNBC and validate the prognostic value of tumor-infiltrating lymphocytes (TILs). Methods: Patients with advanced TNBC were randomly assigned 1:1 to receive gemcitabine (1000 mg/m 2 ) on days 1 and 8 plus oral capecitabine (1000 mg/m 2 twice a day) on days 1–14, or gemcitabine (1000 mg/m 2 ) on days 1 and 8 plus carboplatin area under curve 2 on days 1 and 8. The primary endpoint was progression-free survival (PFS). TILs were analyzed by immunohistochemistry. The margin used to establish non-inferiority was 1.2. Results: In all, 187 patients were randomly assigned, with 93 in GX and 94 in GC. Median PFS was 6.1 months in the GX arm compared with 6.3 months in the GC arm. The hazard ratio for PFS was 1.148, and a 95% CI was 0.856–1.539, exceeding the non-inferiority margin of 1.2. The median overall survival (OS) was 21.0 months in the GX arm compared with 21.5 months in the GC arm. The safety profile for the GX regimen was superior to the GC regimen, especially regarding hematological toxicity. Patients with high CD8 + TILs had significantly longer PFS and OS compared with patients with low CD8 + TILs. In the high CD8 + TIL group, the GC arm had prolonged PFS and OS compared with the GX arm. Conclusion: The trial did not meet the prespecified criteria for the primary endpoint of PFS in patients with advanced TNBC. Moreover, the GC regimen showed better efficacy compared with the GX regimen in patients with high CD8 + TILs. However, the GX regimen should be considered in patients who cannot tolerate hematological toxicity. Trial registration: ClinicalTrials.gov identifier: NCT02207335.